Avaliação do impacto tecnológico de organizações por meio da análise de patentes - Silva, Henrique Monte Mor (2022)
The future competition from the corporate world will be for patent property rights. There are several studies in the literature that assess the technological impact of patents, but when it comes to assessing the technological impact of organizations as a result of their patents, there is an evident gap in the literature. The present research is characterized as applied, exploratory, correlational and quantitative. As a method, the theoretical-conceptual method was chosen and, as a data collection instrument, document research. To fill the gap in the literature, the present research aimed to develop a model capable of measuring the technological impact of organizations in terms of their patents and establishing a ranking among them. To test the model’s pertinence, a case study was carried out for which 3 companies from the Brazilian automotive sector, manufacturers of the windshield wiper system, were chosen. The model proposal was elaborated considering important variables identified in the systematic literature review, namely: citations, references, patent families and IPC classifications. The model is based on the analysis of complex networks and uses the PageRank algorithm as a metric. From the application of the model, the technological impact values of the patents of the entire state of the art related to the windshield wiper system were calculated. With this, the technological impacts of the 3 companies were determined and a ranking could be generated between them. The model was able to provide results consistent with the real world. Therefore, this research contributes to practice, providing organizations with a means of identifying their positions, in terms of technological impact, against their competitors; with theory, proposing an unprecedented model in the literature for measuring the technological impact of organizations in any technological area; and with society, because, based on the determination of the technological impact, the search for organizational innovation goals is encouraged, for which people are essential.